Restricted p-Isometry Properties of Partially Sparse Signal Recovery - Haini Bi; Lingchen Kong; Naihua Xiu (Discrete Dynamics in Nature and Society)
By generalizing the restricted p-isometry property to the partially sparse signal recovery problem, we give a sufficient condition for exactly recovering partially sparse signal via the partial lp minimization (truncated lp minimization) problem with p∈(0,1]. Based on this, we establish a simpler sufficient condition which can show how the p-RIP bounds vary corresponding to different ps.